EXPERIENCES AND OPINIONS OF PAEDIATRIC PRESCRIBERS CONCERNING FAST-MELT TABLETS AT BIRMINGHAM CHILDREN'S HOSPITAL NHS FT. Issue 8 (11th July 2014) - Bhachu, J Kaur; Terry, D; Junaid, E
Abstract : Aim: To identify the experiences and opinions of paediatric prescribers regarding Fast-Melt Tablets (FMTs). Method: The study comprised of a single-site, cross-sectional, self-completed questionnaire consisting of 11 questions. The questionnaire included experience-based questions, opinion-based questions and a short educational summary. Participants comprised of medical prescribers (n=26) of various levels (FY1/2, ST1/2, registrars and consultants) and non-medical prescribers (n=7) (independent nurse prescribers and independent pharmacist prescribers). Data was collected from paediatric prescribers at a specialised paediatric hospital on 8th and 21st February 2013 and was collated using Microsoft Excel and Word. FMTs melt onto the tongue and dissolve into the saliva without the need for water.1 They disintegrate and dissolve within 60 seconds of placing onto the tongue and are swallowed with the saliva.2 This formulation is also known as orally disintegrating tablets.3 Results: Response rate of 97% (n=33/34). There were fewer non-medical prescriber respondents (n=7) than medical (n=26). 42% (n=14/33) of the entire cohort had practical experience in prescribing FMTs; 33% (n=11/33) had administered them to patients during their career and 30% (n=10/33) had theoretical awareness of FMTs. Theoretical awareness was defined as an awareness of FMTs without actual experience in prescribing them. Of the prescribers who had practical experience with FMTs, 43% (n=6/14) claimed that there was no reason that prevented them from prescribing FMTs again in the future. However, prescribers who had qualms with the formulation expressed that it was because of patient compliance issues and the lack of availability of FMTs in the hospital. The opinions towards FMTs differed amongst the paediatric prescribers according to their experiences. With regards to prescribing habits, 23% (n=6/26) of prescribers, who had either theoretical or practical experiences with FMTs, claimed that there was no reason that prevented them from prescribing FMTs. However, it was not clear whether these particular respondents would prescribe FMTs again in the future. From those who previously had no awareness (n=7) of FMTs, 3 respondents stated that they would consider prescribing them in the future. From the entire cohort of prescribers, 24% (n=8/33) stated that factors such as patient compliance, costs and hospital guidelines controlled whether they prescribed FMTs in the future. Conclusion: A minority of prescribers had practical experience of using FMTs. Further research is required to understand why prescribers found that patient compliance was a problem with FMTs in order to further appreciate why they are not widely prescribed or administered. In the opinion of respondents it is not clear if they would prescribe FMTs in the future, which may be influenced by non-formulation issues including: hospital guidelines, costs and patient compliance.